Immunodermatology: at a glance - Prakoeswa, Flora Ramona Sigit; Awanis, Ghina Shabrina; Sari, Winda Atika; Pramuningtyas, Ratih (Faculty of Medicine, Universitas Airlangga, 2025)
Background: Immunodermatology is a medical specialty specializing in detecting and treating skin conditions induced by a compromised immune system response. Each cellular element of the skin undergoes a unique developmental process and serves a specific function within the skin. Many disorders affecting epithelial organs, including the skin, mucous membranes, digestive tract, and respiratory tracts, require immunodermatological testing for diagnosis and treatment. Immunodermatology, a field at the intersection of dermatology and immunology, continues to evolve, with new research being published annually. Purpose: This review aims to summarize the foundational principles of immunodermatology, current diagnostic approaches, and selected immune-mediated skin disorders. Review: There are numerous dermatological conditions related to immunodermatology. Advances in immunology and dermatology have enhanced our understanding of the skin as an active immune organ. Immunodermatology encompasses a wide range of diseases involving both innate and adaptive immunity. Despite growing research, many aspects remain under investigation. Conclusion: The skin’s immunological function could be viewed as a complex and multifaceted interplay between signal processing and defense reactions. Immunodermatology continues to expand with ongoing innovations in diagnostics and therapeutics, highlighting its importance in future clinical and research developments.